The utility of low energy availabilty in females questionnaire to detect markers consistent with low energy availability-related conditions in a mixed-sport cohort - Rogers, M. A.; Drew, M. K.; Appaneal, R.; Lovell, G.; Lundy, B.; Hughes, D.; Vlahovich, N.; Waddington, G.; Burke, L. M. (International Journal of Sport Nutrition and Exercise Metabolism, 2021)
The Low Energy Availability in Females Questionnaire (LEAF-Q) was validated to identify risk of the female athlete triad (triad) in female endurance athletes. This study explored the ability of the LEAF-Q to detect conditions related to low energy availability (LEA) in a mixed sport cohort of female athletes. Data included the LEAF-Q, SCOFF Questionnaire for disordered eating, dual-energy X-ray absorptiometry-derived body composition and bone mineral density, Mini International Neuropsychiatric Interview, blood pressure, and blood metabolic and reproductive hormones. Participants were grouped according to LEAF-Q score (=8 or <8), and a comparison of means was undertaken. Sensitivity, specificity, and predictive values of the overall score and subscale scores were calculated in relation to the triad and biomarkers relevant to LEA. Fisher`s exact test explored differences in prevalence of these conditions between groups. Seventy-five athletes (18-32 years) participated. Mean LEAF-Q score was 8.0 ± 4.2 (55% scored =8). Injury and menstrual function subscale scores identified low bone mineral density (100% sensitivity, 95% confidence interval [15.8%, 100%]) and menstrual dysfunction (80.0% sensitivity, 95% confidence interval [28.4%, 99.5%]), respectively. The gastrointestinal subscale did not detect surrogate markers of LEA. LEAF-Q score cannot be used to classify athletes as "high risk" of conditions related to LEA, nor can it be used as a surrogate diagnostic tool for LEA given the low specificity identified. Our study supports its use as a screening tool to rule out risk of LEA-related conditions or to create selective low-risk groups that do not need management as there were generally high negative predictive values (range 76.5-100%) for conditions related to LEA.